1998
DOI: 10.1038/sj.mp.4000421
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperactivity medication: methylphenidate and amphetamine

Abstract: How do 'stimulants' reduce hyperactivity in children and adults? How can drugs which raise extracellular dopamine result in psychomotor slowing of hyperactive children when dopamine is known to enhance motor activity, such as in Parkinson's disease? These apparent paradoxes are the focus of this brief review on the mechanism of action of stimulant medications used in the treatment of children, and of an increasing number of adults who meet diagnostic criteria for attention deficit hyperactivity disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(158 citation statements)
references
References 65 publications
6
150
0
2
Order By: Relevance
“…This gene is of particular interest, as the transporter is the principal target for methylphenidate and other psychostimulant medication used to treat patients with ADHD (Volkow et al 1998;Seeman and Madras 1998). Cook et al (1995) reported an association between the 480bp DAT1 allele, one of the common alleles of a 40bp repeat situated in the 3 Ј untranslated region of the DAT1 gene which maps to 5p15.3 and ADHD.…”
Section: Converging Evidence Has Implicated Abnormalities Of Dopaminementioning
confidence: 99%
“…This gene is of particular interest, as the transporter is the principal target for methylphenidate and other psychostimulant medication used to treat patients with ADHD (Volkow et al 1998;Seeman and Madras 1998). Cook et al (1995) reported an association between the 480bp DAT1 allele, one of the common alleles of a 40bp repeat situated in the 3 Ј untranslated region of the DAT1 gene which maps to 5p15.3 and ADHD.…”
Section: Converging Evidence Has Implicated Abnormalities Of Dopaminementioning
confidence: 99%
“…The literature on psychostimulant drugs, however, is mixed (Seeman and Madras, 1998). For instance, opposite effects are found for amphetamine in the delay task (Evenden and Ryan, 1996;Wade et al, 2000).…”
Section: Impulsivity and Novelty Seekingmentioning
confidence: 99%
“…Current hypotheses on the biological basis of ADHD have centered on the dysregulation of frontostriatal circuits and the neurotransmitters involved in these pathways. In particular, accumulating evidence implicate altered dopamine signalling in the disorder (Davids et al, 2003;Durston, 2003;Seeman and Madras, 1998;Viggiano et al, 2003) and genetic association of several genes engaged in dopamine signalling is supported by meta-analysis of pooled data (e.g. DRD4, DRD5, DAT1, and SNAP25) (Thapar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%